Analisis Rasio Kinerja Keuangan Pemerintah Kota Medan Tahun 2014-2018 - Listya Devi Junaidi; Malesa Anan (Ekonomis: Journal of Economics and Business, 2021)
It is very important to measure financial performance to assess the accountability of local governments in managing regional finances. Accountability is not just the ability to show how public money is spent but includes the ability to show how public money is spent efficiently, effectively and economically. The problem that is currently being faced by the Medan City Government is the fluctuating percentage of PAD achievement of the Medan City Government from 2014 – 2018. This study aims to determine the financial performance of Medan City measured based on the Regional Financial Independence Ratio Analysis, PAD Effectiveness Ratio, PAD Efficiency Ratio, Ratio Degree of Fiscal Decentralization, Growth Ratio and Harmony Ratio for the period 2014-2018. This study uses a quantitative descriptive method that is doing calculations on the financial data obtained to solve problems that occur by analyzing the ratio of regional financial independence, PAD effectiveness ratio, PAD efficiency ratio, fiscal decentralization degree ratio, growth ratio and compatibility ratio. The results of this study indicate that the financial performance of the Medan City Government is quite good from the aspect of independence with the "participatory" category, then from the aspect of the effectiveness ratio and efficiency ratio, it is still necessary to pay attention again because the average ratio results show the category of being less effective and less efficient. On the aspect of the degree of decentralization, the results show a "medium" category where the amount of PAD contributes quite well to regional income in Pemko Medan. The resulting compatibility ratio shows that the percentage of the use of APBD for operational expenditure is higher at 76.7% compared to capital expenditure, which is 23.2%. The results of the regional income and expenditure growth ratio in the Medan City Government have decreased and increased every year.